(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Well-preserved and abundant plant megafossils were found at in the basal part of the Shemshak Formation in on Ozon Mountain, Alborz, NE Iran .Persicostrobus is a new equisetalean strobilus which is introduced from the Rhaetian (Upper Triassic) strata. Persicostrobus ghavideli is introduced described as the type species of this genus. Persicostrobus sp. is an immature cone of this genus.